Evaluasi Usability Pada Sistem Monitoring Pengadaan Menggunakan Metode Usability Testing (Studi Kasus PT Pembangkitan Jawa-Bali) - Achmad Isa Anshori; Himawat Aryadita; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PT Pembangkitan Jawa-Bali (PJB) Surabaya is a subsidiary of PT Perusahaan Listrik Negara (PLN) that worked in the provision of electrical energy of high quality, reliable and eco-friendly. One of the units contained in PT PJB is the Unit Bisnis Jasa Operation & Maintenance Luar Jawa-2 (UJLJ-2) which is tasked to conduct goods and services procurement activities on electrical assets in the generating unit. In carrying out its activities, UJLJ-2 is equipped with an information system to reconstruct procurement data from start to finish called Procurement Monitoring System (SIMOP). However, in the operation, there was found the constraint that users feel difficult when using SIMOP due to different user backgrounds and not yet able to adapt to the system, and therefore the evaluation of usability is needed to find out how easy the system can be used by the user. By using the method of Usability Testing with Nielsen model and based on three criteria of Efficiency, Error, and Satisfaction, the evaluation is done by testing the task scenario, interview, and post-Study System Usability Testing (PSSUQ) questionnaire to SIMOP users. From the result of evaluation of usability we got the value for Efficiency criteria equal to 58,5% that not high enough, value of Error criteria equal to 4,5% that means few errors, and value for Satisfaction criteria equal to 74,5% that means high enough.